ISSUES OF FOREIGN LOBBYING IN INTERNATIONAL RELATIONS (Вісник: Міжнародні відносини, 2021)
The promotion of the interests of national governments through the foreign states, as well as the lobbying of the interests of third countries in international organizations has gone beyond classical diplomatic relations and is increasingly taking place through modern means and forms of lobbying. The paper examines the aspects of foreign lobbying regulation and recommendations of Council of Europe experts on the implementationof legislation, including in the field of international lobbying. The essence of the concept of "foreign lobbying" is highlighted and the key means of indirect foreign lobbying are investigated.
Keywords: foreign lobbying, foreign influence, international lobbying, OECD